Association between the triglyceride glucose-waist circumference index and cardiovascular disease across different glycemic statuses among middle-aged and older Chinese adults - Cui, Yuyu; Xu, Zhening; Ding, Lijuan; Li, Yanju; Zhou, Xiaoyan; Li, Lingxia (Frontiers in Cardiovascular Medicine, 2025)
IntroductionThis study aims to systematically investigate the association between the triglyceride-glucose index multiplied by waist circumference (TyG-WC) and the risk of cardiovascular disease (CVD) and further explore how this relationship varies across different glycemic statuses, including normal glucose regulation (NGR), prediabetes (Pre-DM), and diabetes mellitus (DM).MethodsData were obtained from the China Health and Retirement Longitudinal Study (CHARLS), including a total of 7,812 middle-aged and older adults. Kaplan–Meier survival analysis, multivariable Cox proportional hazards models, and restricted cubic spline (RCS) regression were employed to assess the association between baseline TyG-WC and incident CVD risk. Subgroup analyses were conducted based on glucose metabolism status to evaluate potential heterogeneity in the associations.ResultDuring an average follow-up period of 8.25 years, a total of 1,638 incident CVD events were recorded, corresponding to a cumulative incidence of 20.97%. Kaplan–Meier curves showed that individuals in higher TyG-WC strata had significantly greater cumulative CVD incidence compared to those in lower strata across all glucose metabolism categories (log-rank test, P < 0.05). After adjusting for potential confounders, the hazard ratios (HRs) [95% confidence intervals (CIs)] for CVD in the second, third, and fourth TyG-WC quartiles (Q2–Q4) were 1.20 (1.05–1.37), 1.30 (1.14–1.49), and 1.54 (1.34–1.77), respectively, compared to Q1. In the NGR and Pre-DM groups, TyG-WC was positively and linearly associated with CVD risk. In contrast, a significant non-linear association was observed in the DM group (P for non-linear = 0.046). Specifically, TyG-WC was positively associated with CVD risk when values were below 816.16, whereas above this threshold the increased risk plateaued and was no longer statistically significant.ConclusionTyG-WC is a practical and effective metabolic indicator for evaluating CVD risk among middle-aged and older Chinese adults. Its clinical application may facilitate early identification and precise stratification of high-risk individuals, thereby providing strong support for CVD prevention and targeted intervention strategies.